An Evaluation of Training Availability in Creating Awareness for Psychosocial Risk Management Best Practice within the European Union. - Fadipe, Tolulope G (2011)
The aim of this study is to evaluate the level of compliance of the PRIMA-EF best practice guidelines by assessing the psychosocial risk management topics covered by various training programmes across some countries within the European Union. The data obtained was from a group of PRIMA-EF project partners who wanted to find out if there were gaps between psychosocial risk management policies and best practice.